Electrochemical Immunosensor for Sensitive Determination of TGF β1 in Urine. (2017) - Sánchez-Tirado, E.; González-Cortés, A.; Yánez-Sedeño, P.; Pingarrón, J.M.
Abstract: The first amperometric immunosensor for the quantification of TGF– β 1 is described in this work. The immunosensor design involves disposable devices using carboxylic acid–functionalized magnetic microparticles supported onto screen–printed carbon electrodes and covalent immobilization of the specific antibody for TGF– β 1 using Mix&Go TM polymer. A sandwich–type immunoassay was performed using peroxidase–labeled streptavidin (Poly–HRP–Strept) polymer for signal amplification. The calibration plot allowed a range of linearity extending between 15 and 3000 pg/mL TGF– β 1 (LOD 10 pg/mL). The usefulness of the immunosensor was evaluated by analyzing spiked urine at different pg/mL concentration levels.